PROSEDUR PENERJEMAHAN METAFORA KONSEPTUAL DALAM PIDATO PRESIDEN JOKO WIDODO - Hakim, Amirul; Sutrisno, Adi (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
This research aims to examine how interpreters translate conceptual metaphors in President Joko Widodo's speech during the 2022 G20 Summit meeting in Bali. This research used the basic conceptual metaphor theory of Lakoff and Johnson (1980) and the metaphor translation theory by Broeck (1981) in its analysis. This research is descriptive research with a qualitative approach. The data source in this research was taken from President Joko Widodo's speech at the G20 Summit in Bali, which KOMPASTV uploaded. This research has three stages: data provision stage, data analysis stage, and data analysis results presentation stage. The researcher found 76 conceptual metaphor data from the study in President Joko Widodo's speech at the 2022 G20 Summit meeting. Of the 76 conceptual metaphors found, there are 53 (69.7%) metaphors translated with the same imagery, 13 (17.1%) metaphors translated with different imagery, and 10 (13.2 %) metaphors had their imagery removed. Most of the metaphors in this speech were translated while maintaining ST's original image (69.7%).